Устройство для моделирования трехфазной линии электропередачи с распределенными параметрами - Боровиков Ю. С. Юрий Сергеевич; Сулайманов А. О. Алмаз Омурзакович; Гордиенко И. С. Иван Сергеевич; Гусев А. С. Александр Сергеевич; Свечкарев С. В. Сергей Владимирович; Андреев М. В. Михаил Владимирович; Рубан Н. Ю. Николай Юрьевич; Прутик А. Ф. Алексей Фёдорович
опубл. 10.12.12